Effect of chitosan edible coating containing anthocyanins and tea polyphenols on cold storage of chilled pork - Chen, Han; Zhang, Fang; Yang, Yi-xin; Meng, Xiu-hua; Ding, Xiao-qin; Jian, Tun-yu; Niu, Guan-ting; Tong, Bei; Gai, Ya-nan; Lü, Han; Chen, Jian (Frontiers in Nutrition, 2025)
Preserving fresh meat has been a long-standing challenge due to microbial growth and lipid oxidation. In this study, chitosan (CS) active coatings loaded with blackberry anthocyanins (BA), tea polyphenols (TP), and their combination, designated as CS/BA, CS/TP, and CS/BA/TP, were applied for chilled pork preservation. Compared to CS coating alone, CS/BA/TP coating exhibited a 9.3% lower total viable count (TVC), a 45.5% reduction in thiobarbituric acid reactive substances (TBARS), and a 26.6% decrease in total volatile basic nitrogen (TVB-N) after 12 days of storage at 4°C. Furthermore, the combined use of TP and BA exhibited a synergistic effect, with the most pronounced impact observed in oxidative stability, while also improving microbial inhibition and maintaining color stability. These results highlight CS/BA/TP coatings as a promising natural preservative for extending chilled pork shelf life.